2014
DOI: 10.1214/14-aos1218
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric ridge estimation

Abstract: We study the problem of estimating the ridges of a density function. Ridge estimation is an extension of mode finding and is useful for understanding the structure of a density. It can also be used to find hidden structure in point cloud data. We show that, under mild regularity conditions, the ridges of the kernel density estimator consistently estimate the ridges of the true density. When the data are noisy measurements of a manifold, we show that the ridges are close and topologically similar to the hidden … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 40 publications
4
158
0
Order By: Relevance
“…A kernel density ridge can be used to completely describe a biased version, called a surrogate, of a manifold embedded in R D given sufficient samples and bounded noise [20]. The main motivation for using density ridges to locally unwrap nonlinear manifolds comes from the following.…”
Section: Motivation: Using Density Ridges To Unwrap Manifoldsmentioning
confidence: 99%
See 4 more Smart Citations
“…A kernel density ridge can be used to completely describe a biased version, called a surrogate, of a manifold embedded in R D given sufficient samples and bounded noise [20]. The main motivation for using density ridges to locally unwrap nonlinear manifolds comes from the following.…”
Section: Motivation: Using Density Ridges To Unwrap Manifoldsmentioning
confidence: 99%
“…Of great value is the recent paper by Genovese et al, [20], which showed that the Hausdorff distance between a d-dimensional manifold embedded in D dimensions and the d-dimensional ridge of the density is bounded under certain restrictions wrt. noise and the closeness of the density estimate to the true density.…”
Section: Principal Curves and Density Ridgesmentioning
confidence: 99%
See 3 more Smart Citations